The effect of an informal caregiver's programme on the care of patients infected with HIV/AIDS - Zulu, Nompumelelo Patience (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MCur (Interdisciplinary Health Sciences. Nursing Science))--University of Stellenbosch, 2010.